The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1159/000318877
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Ranibizumab and Bevacizumab in Combination with Full-Fluence Verteporfin Therapy and Dexamethasone for Exudative Age-Related Macular Degeneration

Abstract: Purpose: To evaluate the efficacy and safety of triple therapy with intravitreal anti-vascular-endothelial-growth-factor (VEGF) antibody, dexamethasone and verteporfin photodynamic therapy (PDT) for exudative age-related macular degeneration (AMD). Methods: Retrospective, comparative, interventional study. Records of treatment-naïve patients who received intravitreal bevacizumab or ranibizumab in monotherapy or in combination with dexamethasone and full-fluence verteporfin PDT in triple therapy were reviewed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…A single session of TT led to complete resolution of angiographic evidence of CNV in 77.8% of cases [10]. Forte et al [12] reviewed retrospectively the efficacy of PDT-V (50 J/cm 2 ), intravitreal dexamethasone and ranibizumab or bevacizumab in 21 eyes. They reported a significant improvement of VA and foveal thickness with a mean follow-up of 14 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single session of TT led to complete resolution of angiographic evidence of CNV in 77.8% of cases [10]. Forte et al [12] reviewed retrospectively the efficacy of PDT-V (50 J/cm 2 ), intravitreal dexamethasone and ranibizumab or bevacizumab in 21 eyes. They reported a significant improvement of VA and foveal thickness with a mean follow-up of 14 months.…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy with anti-VEGF agents, steroids and PDT-V has been proposed to interfere with multiple stimuli to pathologic vascular proliferation while reducing treatment frequency [8,9,10,11]. In previously published triple-therapy studies, PDT-V light fluence ranged from 25 to 50 J/cm 2 [8,9,10,11,12,13,14]. It has been shown that reducing the fluence and/or irradiance of light delivered can enhance the selectivity of PDT-V treatment, avoiding collateral damage to the physiologic choroid [15].…”
Section: Introductionmentioning
confidence: 99%
“…A few other reports have suggested a possible role of dexamethasone in combination with anti-VEGF therapies [45,46]. Studies exploring the combination of verteporfin PDT, anti-VEGF and intravitreal dexamethasone failed to show superior visual outcomes when compared to anti-VEGF monotherapy [47][48][49].…”
Section: Combination Therapiesmentioning
confidence: 99%
“…A recent study (Forte et al, 2011) compared PDT + dexamethasone + anti-VEGF (Ranibizumab or Bevacizumab) triple therapy with Ranibizumab or Bevacizumab monotherapy. Sixty-one eyes were included in the first group and 40 in the second.…”
Section: Other Studiesmentioning
confidence: 99%